The Impact of Social Media On Belief Formation - Marco A. Schwarz (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2017)
Social media are becoming increasingly important in our society and change the way people communicate, how they acquire information, and how they form beliefs. Experts are concerned that the rise of social media may make interaction and information exchange among like-minded individuals more pronounced and therefore lead to increased disagreement in a society. This paper analyzes a learning model with endogenous network formation in which people have different types and live in different regions. I show that when the importance of social media increases, the amount of disagreement in the society first decreases and then increases. Simultaneously people of the same type hold increasingly similar beliefs. Furthermore, people who find it hard to communicate with people in the same region may interact with similar people online and consequently hold extreme beliefs. Finally, I propose a simple way to model people who neglect a potential correlation of signals and show that these people may be made worse off by social media.
Keywords: C72; D72; D83; D85; Z10; Z19; 330; social media; network formation; social learning; polarization; homophily; correlation neglect